"Breathing" Motion of a Modulable Molecular Cavity. Issue 27 (20th April 2017) - Zhang, Dawei; Cochrane, James Robert; Di Pietro, Sebastiano; Guy, Laure; Gornitzka, Heinz; Dutasta, Jean‐Pierre; Martinez, Alexandre
Abstract: A class of hemicryptophane cages that adopt imploded conformations in solution and in the solid state has been described and studied by NMR spectroscopy and X‐ray crystallography. It is reported that the degree of collapse of the molecular cavity can be controlled by changing the stereochemistry of the chiral elements of the hemicryptophanes, leading to a modulation of their physical and chemical properties. Upon the binding of an oxidovanadium unit, the collapsed molecular cavity can inflate to give an expanded conformation. Removal of the vanadium core by an ancillary complexing ligand restores the initial folded structure. Thus, coordination/de‐coordination of the metal ion controls the dynamic motions of the cage, leading to a reversible nanomechanical process. This controlled motion between a collapsed and expanded cavity can be seen as that of a breathable molecular cage. Abstract : The expandables : The class of hemicryptophane cages that adopt imploded conformations in solution and in the solid state has been described and studied by NMR and X‐ray crystallography. Fully collapsed molecular cages can re‐inflate after metal complexation. This motion is reversible and several cycles can be performed. The controlled motion between a collapsed and expanded cavity can be seen as that of a breathable molecular cage.